EVALUASI PENGGUNAAN CHEMICAL MODIFIER PADA ANALISIS LOGAM DAN SEMI LOGAM DENGAN GRAPHITE FURNACE ATOMIC ABSORPTION SPECTROMETRY - Rosi Ketrin (Research Center for Chemistry - LIPI, 2015)
Graphite Furnace Atomic Absorption Spectrometry (GF-AAS) is not a new method in chemical analysis, especially for metals and metalloids, unfortunately there are a lot of laboratories in Indonesia that still not used it correctly, whereas if used it correctly, the method will be an excellent and can be a reference method. This review focus on the kinds of interferences in the GF-AAS such as spectral, physic and chemical interferences and alsoon the use of a lot of kinds of chemical modifier that very important part in analysis by GF-AAS, however it is often unused because of the difficulty. It is noted that highest absorption level from each analyte is different even though used the same modifier and ashing temperature, therefore the selection of chemical modifier is important to find the appropriate modifier for each analyte and their matrixes.Keyword: GF-AAS, spectral interferences, physic interferences, chemical interferences, chemical modifier